ASUHAN KEPERAWATAN NYERI AKUT PADA PASIEN POST OPERASI SECTIO CAESAREA DENGAN TERAPI RELAKSASI AUTOGENIK - Mona Santika; Siska Iskandar (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
Sectio Caesarea is a fragmented tissue or skin that stimulates the sensory area and stimulates the safety of sensory areas, resulting in and other neurological injuries can be a risk of infection if the opening of tissues and lack of treatment cause bacteria to enter through operating wounds. The purpose of the research aims to illustrate the acute nursing care of a post section Caesarea with autogenic relaxation therapy. Methodelogythis research is deductive with a qualitative approach and case study design with acute pain disorders in post section cesarean with autogenic relaxation therapy. The result is maternal screening indicates a scale of 3 pain, acute pain like gangstas, pain scale 3, pain that is felt constantly on the move and is impeded by mobility, activity interrupted. Vital Sign is within normal limits, the action done by performing an autogenic relaxation to treat post pain, after three days of nursing and treatment of the subject data has cooled down on both sides.Keywords:Â Sectio-Caesarea, nursing care, pain disorder